2019
DOI: 10.1503/cmaj.180053
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and managing younger women at high risk of cardiovascular disease

Abstract: C ardiovascular disease (CVD), which is largely preventable, is a leading cause of morbidity and mortality among Canadian women. For this article, we use CVD to refer to ischemic heart disease and stroke. Data for peripheral arterial disease in women are limited and are addressed elsewhere. 1 Until now, risk reduction has focused largely on postmenopausal woman with traditional risk factors: diabetes, smoking, hypertension and hyperlipidemia. Consequently, CVD mortality has declined, largely driven by those ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…CVDs are a group of disorders of the heart and blood vessels 7. They are generally classified as atherosclerotic CVDs (related to atherosclerosis of arteries that supply organs (coronary heart disease, cerebrovascular disease and peripheral arterial diseases)8 and non-atherosclerotic CVDs that include rheumatic heart disease, congenital heart disease, cardiomyopathies and others 9…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CVDs are a group of disorders of the heart and blood vessels 7. They are generally classified as atherosclerotic CVDs (related to atherosclerosis of arteries that supply organs (coronary heart disease, cerebrovascular disease and peripheral arterial diseases)8 and non-atherosclerotic CVDs that include rheumatic heart disease, congenital heart disease, cardiomyopathies and others 9…”
Section: Introductionmentioning
confidence: 99%
“…Most CVDs are preceded by many years of cardiovascular risk factors. Early detection and treatment of modifiable risk factors can lower an individual’s risk of developing CVD 2 9. Modifiable risk factors are those conditions for which interventions exist to reduce their levels and decrease the occurrence of CVDs.…”
Section: Introductionmentioning
confidence: 99%
“…Low CVD risk factors (i.e., lipid and blood pressure) may lead to underestimation of subsequent lifetime risk amongst the relatively young women in the FHRPC. It is not known whether better lifetime CVD risk assessment tools could increase engagement amongst young women [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we included more studies that had a length of follow-up greater than 10 years and found that among women who participated in such studies, the risk of diabetes was greatest at age 35-40 years. Further, several studies have found a relationship between HDP and future CVD [22,23,27,[48][49][50][51]. A large population-based retrospective cohort All included studies in the meta-analysis have controlled for baseline diabetes mellitus aHR = pooled adjusted hazard ratios, reference groups = no history of HDP a Studies that controlled for GDM either by exclusion or regression b Studies that followed women from the time of delivery (mean age: 28.2 years, range: 25-33 years) GH, gestational hypertension; HTN, hypertension; PEC, pre-eclampsia study found that maternal placental syndromes, including HDP and placental abruption, were associated with a twofold increase in CVD compared with those without maternal placental syndrome, with the mean age of onset of 38 years [52].…”
Section: Discussionmentioning
confidence: 99%